1990
DOI: 10.1021/bi00494a021
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the EcoRV restriction endonuclease with the deoxyadenosine and thymidine bases in its recognition hexamer d(GATATC)

Abstract: A set of dA and T analogues suitable for the study of protein DNA interactions have been incorporated into the central d(ATAT) sequence within d(GACGATATCGTC). The individual analogues have one potential protein contact (either a hydrogen-bonding group or a CH3 group capable of a van der Waals interaction) deleted. In general, the modified bases do not perturb the overall structure of the dodecamer, enabling results obtained to be simply interpreted in terms of loss of protein DNA contacts. We have used the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 38 publications
6
46
0
Order By: Relevance
“…In the cognate complex, the protein makes extensive hydrogen-bonding contacts with the bases in the DNA major groove; these contacts are absent in the non-cognate complex and the corresponding protein elements are largely disordered. The observed protein-base contacts are generally consistent with those inferred from biochemical studies on the effects of modi®ed DNA bases (Mazzarelli et al, 1989;Newman et al 1990b;Waters & Connolly, 1994). In summary, the cognate complex in the absence of Mg 2 appears to have all the structural properties expected for a speci®c recognition complex, but the non-cognate complex does not.…”
Section: Introductionsupporting
confidence: 77%
“…In the cognate complex, the protein makes extensive hydrogen-bonding contacts with the bases in the DNA major groove; these contacts are absent in the non-cognate complex and the corresponding protein elements are largely disordered. The observed protein-base contacts are generally consistent with those inferred from biochemical studies on the effects of modi®ed DNA bases (Mazzarelli et al, 1989;Newman et al 1990b;Waters & Connolly, 1994). In summary, the cognate complex in the absence of Mg 2 appears to have all the structural properties expected for a speci®c recognition complex, but the non-cognate complex does not.…”
Section: Introductionsupporting
confidence: 77%
“…We have observed a similar improvement in binding at position 12 For this protein-DNA complex, we have presented evidence that supports hydrogen bonding contact sites at positions that are predicted to be directly involved in the formation of the protein-DNA interface. We have also demonstrated that the central region of the operator is responsible, in part, for modulating the protein-DNA complex indirectly and by manipulating these indirect effects with 'anomalous' base pairs a protein-DNA complex more stable than the wild-type operatorrepressor was achieved.…”
Section: The Role Of the Central Region Of The Operatorsupporting
confidence: 69%
“…4 nmol (20 pM) of double-stranded oligodeoxynucleotide (not phosphorylated at the 5'-position) was incubated in 200 p L of 50 mM Hepes, pH 7.5, 10 mM MgC12, 100 mM NaCl, and 10 units (manufacturers units, special grade for molecular biology, obtained from Promega, Southampton, U.K.) of alkaline phosphatase in the presence of 340 pmol (1.7 pM) of endonuclease dimer. The reaction was monitored by reversephase HPLC (Newman et al, 1990a). The alkaline phosphatase removes the 5'-phosphate from one of the products, and this eases separation of the two product oligodeoxynucleotides.…”
Section: Methodsmentioning
confidence: 99%